Evaluation of the Three Economic-Cultural, Social-Political and Security Pillars of Asean Over 55 Years of Operation - Van Trong Dinh; Minh Hiep Ngo; Van Duong Nguyen; Duc Tho Pham; Viet Anh Duong (Current Topics on Business, Economics and Finance Vol. 7, 2023)
The predecessor of ASEAN is an organization called the Association of Southeast Asia (ASA), an alliance established in 1961 consisting of the Philippines, Malaysia and Thailand. Southeast Asia is divided into two groups of rival countries around Cambodia, one is the Indochinese countries and the other is the ASEAN countries. It was only when Vietnam withdrew its troops that ASEAN countries began to resume bilateral relations with Vietnam and welcomed Vietnam’s participation in regional cooperation. The waters of ASEAN are three times as large as land. Over 55 years of establishment and development, this is considered the most successful regional organization on earth. Despite the fact that when it comes to ASEAN, people frequently discuss its accomplishments, in the context of this article, we would like to offer some perspectives on its limitations as a foundation for advice for the organization’s leaders in this study. The world community at large, first of all the industrialized countries, need to help poor countries get out of poverty, disease and underdevelopment.